Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! To find the zeros of the polynomial function [tex]\( f(x) = x^3 + 7x^2 - 9x - 63 \)[/tex] and to determine the multiplicity of each zero, we can follow these detailed steps.
### Step 1: Identify Possible Rational Zeros
We can use the Rational Root Theorem to identify possible rational zeros. The Rational Root Theorem states that any potential rational zero [tex]\( p/q \)[/tex] of the polynomial [tex]\( a_nx^n + a_{n-1}x^{n-1} + \cdots + a_1x + a_0 \)[/tex] must be a factor of the constant term [tex]\( a_0 \)[/tex] divided by a factor of the leading coefficient [tex]\( a_n \)[/tex].
For the polynomial [tex]\( f(x) = x^3 + 7x^2 - 9x - 63 \)[/tex]:
- The constant term [tex]\( a_0 = -63 \)[/tex].
- The leading coefficient [tex]\( a_n = 1 \)[/tex].
The possible rational zeros are the factors of [tex]\(-63\)[/tex]: [tex]\(\pm 1, \pm 3, \pm 7, \pm 9, \pm 21, \pm 63\)[/tex].
### Step 2: Test Potential Zeros
We test these potential zeros by substituting them into the polynomial [tex]\( f(x) \)[/tex] to see if they result in [tex]\( f(x) = 0 \)[/tex].
Let’s start with [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = 3^3 + 7(3^2) - 9(3) - 63 = 27 + 63 - 27 - 63 = 0 \][/tex]
Since [tex]\( f(3) = 0 \)[/tex], [tex]\( x = 3 \)[/tex] is a zero of the polynomial.
### Step 3: Perform Polynomial Division
We will now factor [tex]\( (x - 3) \)[/tex] out of the polynomial using polynomial division or synthetic division.
Using synthetic division to divide [tex]\( x^3 + 7x^2 - 9x - 63 \)[/tex] by [tex]\( x - 3 \)[/tex]:
[tex]\[ \begin{array}{r|rrrr} 3 & 1 & 7 & -9 & -63 \\ & & 3 & 30 & 63 \\ \hline & 1 & 10 & 21 & 0 \\ \end{array} \][/tex]
The quotient is [tex]\( x^2 + 10x + 21 \)[/tex]. So, we now have:
[tex]\[ f(x) = (x - 3)(x^2 + 10x + 21) \][/tex]
### Step 4: Factor the Quadratic
Next, we factor the quadratic [tex]\( x^2 + 10x + 21 \)[/tex].
The quadratic [tex]\( x^2 + 10x + 21 \)[/tex] can be factored into:
[tex]\[ x^2 + 10x + 21 = (x + 3)(x + 7) \][/tex]
Therefore, the complete factorization of the polynomial [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = (x - 3)(x + 3)(x + 7) \][/tex]
### Step 5: Determine Zeros and Their Multiplicities
From the factorized form [tex]\( f(x) = (x - 3)(x + 3)(x + 7) \)[/tex], we can identify the zeros and their multiplicities:
- [tex]\( x = 3 \)[/tex] has a multiplicity of 1.
- [tex]\( x = -3 \)[/tex] has a multiplicity of 1.
- [tex]\( x = -7 \)[/tex] has a multiplicity of 1.
### Summary
The zeros of the polynomial [tex]\( f(x) = x^3 + 7x^2 - 9x - 63 \)[/tex] and their multiplicities are:
[tex]\[ \begin{align*} x = 3 & \quad \text{(multiplicity 1)} \\ x = -3 & \quad \text{(multiplicity 1)} \\ x = -7 & \quad \text{(multiplicity 1)} \end{align*} \][/tex]
### Step 1: Identify Possible Rational Zeros
We can use the Rational Root Theorem to identify possible rational zeros. The Rational Root Theorem states that any potential rational zero [tex]\( p/q \)[/tex] of the polynomial [tex]\( a_nx^n + a_{n-1}x^{n-1} + \cdots + a_1x + a_0 \)[/tex] must be a factor of the constant term [tex]\( a_0 \)[/tex] divided by a factor of the leading coefficient [tex]\( a_n \)[/tex].
For the polynomial [tex]\( f(x) = x^3 + 7x^2 - 9x - 63 \)[/tex]:
- The constant term [tex]\( a_0 = -63 \)[/tex].
- The leading coefficient [tex]\( a_n = 1 \)[/tex].
The possible rational zeros are the factors of [tex]\(-63\)[/tex]: [tex]\(\pm 1, \pm 3, \pm 7, \pm 9, \pm 21, \pm 63\)[/tex].
### Step 2: Test Potential Zeros
We test these potential zeros by substituting them into the polynomial [tex]\( f(x) \)[/tex] to see if they result in [tex]\( f(x) = 0 \)[/tex].
Let’s start with [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = 3^3 + 7(3^2) - 9(3) - 63 = 27 + 63 - 27 - 63 = 0 \][/tex]
Since [tex]\( f(3) = 0 \)[/tex], [tex]\( x = 3 \)[/tex] is a zero of the polynomial.
### Step 3: Perform Polynomial Division
We will now factor [tex]\( (x - 3) \)[/tex] out of the polynomial using polynomial division or synthetic division.
Using synthetic division to divide [tex]\( x^3 + 7x^2 - 9x - 63 \)[/tex] by [tex]\( x - 3 \)[/tex]:
[tex]\[ \begin{array}{r|rrrr} 3 & 1 & 7 & -9 & -63 \\ & & 3 & 30 & 63 \\ \hline & 1 & 10 & 21 & 0 \\ \end{array} \][/tex]
The quotient is [tex]\( x^2 + 10x + 21 \)[/tex]. So, we now have:
[tex]\[ f(x) = (x - 3)(x^2 + 10x + 21) \][/tex]
### Step 4: Factor the Quadratic
Next, we factor the quadratic [tex]\( x^2 + 10x + 21 \)[/tex].
The quadratic [tex]\( x^2 + 10x + 21 \)[/tex] can be factored into:
[tex]\[ x^2 + 10x + 21 = (x + 3)(x + 7) \][/tex]
Therefore, the complete factorization of the polynomial [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = (x - 3)(x + 3)(x + 7) \][/tex]
### Step 5: Determine Zeros and Their Multiplicities
From the factorized form [tex]\( f(x) = (x - 3)(x + 3)(x + 7) \)[/tex], we can identify the zeros and their multiplicities:
- [tex]\( x = 3 \)[/tex] has a multiplicity of 1.
- [tex]\( x = -3 \)[/tex] has a multiplicity of 1.
- [tex]\( x = -7 \)[/tex] has a multiplicity of 1.
### Summary
The zeros of the polynomial [tex]\( f(x) = x^3 + 7x^2 - 9x - 63 \)[/tex] and their multiplicities are:
[tex]\[ \begin{align*} x = 3 & \quad \text{(multiplicity 1)} \\ x = -3 & \quad \text{(multiplicity 1)} \\ x = -7 & \quad \text{(multiplicity 1)} \end{align*} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.